Sulfated archaeal glycolipid archaeosomes as a safe and effective vaccine adjuvant for induction of cell-mediated immunity. Issue 12 (2nd December 2017) - McCluskie, Michael J.; Deschatelets, Lise; Krishnan, Lakshmi
ABSTRACT: Archaeosomes are liposomal vesicles composed of ether glycerolipids unique to the domain of Archaea . Unlike conventional ester-linked liposomes, archaeosomes exhibit high stability and possess strong adjuvant and immunostimulatory properties making them an attractive vaccine delivery vehicle. Traditionally comprised of total polar lipids (TPL) or semi-synthetic phospho-glycerolipids of ether-linked isoprenoid phytanyl cores with varied glycol- and amino-head groups, archaeosomes can induce robust and long-lasting humoral and cell-mediated immune responses against antigenic cargo and provide protection in murine models of infectious disease and cancer. However, traditional TPL archaeosome formulations are relatively complex comprising several lipid species. Semi-synthetic archaeosomes tested previously contain a combination of several phospho-glycolipids (negative and neutral charged) to produce a stable, uniform-sized liposome formulation. Moreover, they involve many synthetic steps to arrive at the final desired glycolipid composition. Herein, we present a novel adjuvant formulation comprising a sulfated saccharide group covalently linked to the free sn -1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA). SLA individually or mixed with uncharged glyolipid (lactosylarchaeol, LA) constituted efficacious carrier vesicles for entrapped antigens (ovalbumin or melanoma associated tyrosinase-related protein 2 [TRP-2]) and induction of strong cell-mediated responses in mice and protection against subsequent B16 melanoma tumor challenge. Thus, semi-synthetic sulfated glycolipid archaeosomes represent a new class of adjuvants that will potentially ease manufacturing and scale-up, while retaining immunostimulatory activity.